2023
DOI: 10.1002/jaba.1010
|View full text |Cite
|
Sign up to set email alerts
|

Resurgence of destructive behavior following differential rates of alternative reinforcement

Abstract: Behavioral momentum theory (BMT) suggests that resurgence of destructive behavior may be at least partly determined by the rate of alternative reinforcement, with lean schedules of reinforcement producing less resurgence than dense schedules. Findings from basic and translational studies have been mixed, and the effects of alternative reinforcement rate on resurgence remain unclear. In the current study, we conducted a within‐subject evaluation of resurgence during extinction with four children following funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
(104 reference statements)
0
0
0
Order By: Relevance
“…We examined variables that were specifically chosen because of their putative (but sometimes inconsistent; Greer et al, 2023; Irwin Helvey et al, 2023) relation to resurgence found in basic, translational, and/or applied analyses of resurgence (e.g., Fisher et al, 2019; Podlesnik & Shahan, 2009; Shahan et al, 2020; Smith & Greer, 2022; Winterbauer et al, 2013). Our results are consistent with findings from Greer et al (2020, 2023) and Irwin Helvey et al (2023), suggesting that treatment duration may not affect resurgence of challenging behavior. In addition, there was no apparent relation between resurgence magnitude and the other variables analyzed (i.e., phase duration, response rate, and obtained reinforcement).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We examined variables that were specifically chosen because of their putative (but sometimes inconsistent; Greer et al, 2023; Irwin Helvey et al, 2023) relation to resurgence found in basic, translational, and/or applied analyses of resurgence (e.g., Fisher et al, 2019; Podlesnik & Shahan, 2009; Shahan et al, 2020; Smith & Greer, 2022; Winterbauer et al, 2013). Our results are consistent with findings from Greer et al (2020, 2023) and Irwin Helvey et al (2023), suggesting that treatment duration may not affect resurgence of challenging behavior. In addition, there was no apparent relation between resurgence magnitude and the other variables analyzed (i.e., phase duration, response rate, and obtained reinforcement).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Greer et al (2023) recently found that increases in treatment duration did not correspond with decreases in resurgence magnitude in an applied context. Irwin Helvey et al (2023) also recently demonstrated that programming leaner rates of reinforcement during treatment did not mitigate resurgence to a greater degree than programming denser rates, running counter to some prior work in this area (e.g., Fisher et al, 2018). More research is needed to bridge the basic–applied research continuum and investigate the degree to which the relations between these variables and resurgence are evident in clinical settings.…”
mentioning
confidence: 84%
“…See Table 1 for participant demographic information and functions of destructive behavior targeted. One participant, Kendall, participated in a separate study evaluating resurgence during extinction following differential rates of alternative reinforcement (Irwin Helvey et al, 2023) prior to the current experiment.…”
Section: Experiments 2: Counterbalanced Progression Of Reductions In ...mentioning
confidence: 99%